Prevalence of subfertility and associated factors in Jaffna District, Sri Lanka: A cross sectional study - Raguraman, S.; Balagobi, B.; Yaalini, S.; Powsiga, U.; Shribavan, K.; Kiruththiga, T.; Rajeev, G.; Kumaran, S. (The Sri Lanka Medical Association, 2023)
Subfertility is an emerging health problem in Sri Lanka, associated with many factors. Most subfertility issues can be dealt with excellent efficacy of early detection and management. The unavailability of the prevalence and associated subfertility factors in the Jaffna district paved the way for conducting a community-based crosssectional descriptive study among women aged 18 to 49 years, Tamil speaking, and residents in the same household for at least six months. A multi-stage cluster sampling approach was used through the medical officer of health, followed by the public health midwife area. Twenty households were selected in each cluster to collect data on socio-demographic characteristics, selected disease conditions, information related to subfertility, including the risk of male and female factors, and psychological well-being status. Statistical analysis was carried out using SPSS (V25) software. Prevalence and associated risk factors were calculated. The response rate was 85.8%. Prevalence of subfertility was 23.1%. Primary and secondary subfertility were observed in 18.8% and 4.4%, respectively. In total, males have a slightly higher mean age than females, 40.8(4.2). Most were Sri Lankan Tamil, and Hindus of both sexes. Diabetic mellitus and thyroid gland diseases in women are statistically associated with subfertility (p<0.05). This study showed an increased subfertility prevalence in the Jaffna district, Sri Lanka. In this context, the increasing prevalence of subfertility is an eye-opener to the healthcare system and policymakers to concentrate on subfertility care in Sri Lanka.
Keywords: Prevalence; Jaffna; Subfertility